A comparative study on the health-promoting behaviors of patients with and without hypertensive heart disease in Iran - Parastoo Baharvand; Farideh Malekshahi; Nafiseh Gheydar (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Health-promoting behaviors can affect the psychological and physical consequences of hypertension. For the prevention and control of hypertension, lifestyle modification has been recommended. This study aimed to investigate the health-promoting behaviors of patients with hypertensive heart disease in Iran and compare them with those of healthy people. MATERIALS AND METHODS: This was a descriptive comparative study with cross-sectional design. Participants were 141 patients with hypertensive heart disease (mean age = 39 ± 10.2 years) referred to the cardiac clinic of Madani Hospital in Khorramabad, Iran, and 141 healthy people selected from those referred to the hospital. The Persian version of the revised Health-Promoting Lifestyle Profile-II (HPLP-II) was used to evaluate the health-promoting behaviors of participants. After collecting data, they were analyzed in SPSS v. 22 software using descriptive statistics and statistical tests including independent t-test and one-way ANOVA. RESULTS: The overall HPLP-II score was 142.34 ± 30.48 in patients and 150.52 ± 37.07 in controls. The highest and lowest HPLP-II dimension scores in both groups were related to health responsibility and stress management dimensions. There was a significant difference between groups only in dimensions of nutrition (P = 0.017) and physical activity (P = 0.016), and in the overall score (P = 0.044), whose scores were lower in patients compared to controls. The difference in HPLP-II score of patients with different demographic characteristics (marital status, place of residence, gender, age, educational level, and occupation) was not statistically significant. CONCLUSION: Patients with heart disease caused by high blood pressure in Iran have poorer diet and physical activity compared to healthy people. Educational interventions with a focus on the importance of dietary regime and exercise are recommended for them.